Settlement on Railway Sideline in Surabaya City: Dialectics Perspective of Sosio-Spatial Political Policy - Handayani, Triana Dianita; Geraldy, Galang; Syandana, Lauda; Purwati, Enik; Yakin, M. Ainul (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2026)
The rapid urban development of Surabaya has produced persistent socio-spatial tensions, particularly visible in the emergence and endurance of informal settlements along railway corridors. These settlements reflect a complex dialectic between state-led spatial planning, capital-driven urban modernization, and residents’ everyday spatial practices. This study asks how do socio-spatial policies shape, and are reshaped by, informal settlements along railway-side areas in Surabaya. Using a qualitative case study approach, the research draws on in-depth interviews, documentary analysis, and historical investigation conducted in the Dupak Magersari railway corridor. Guided by Lefebvre’s triadic concept of space, perceived, conceived, and lived space, the analysis reveals three key findings. First, railway-side settlements persist not merely due to economic necessity, but through long-term social attachment and the production of lived space by residents. Second, state policies exhibit a contradictory stance: while formally designating railway corridors as restricted zones, local authorities simultaneously recognize residents’ administrative status and access to basic public services. Third, this policy ambivalence generates a socio-spatial dialectic in which informal settlements are neither fully legalized nor effectively removed, resulting in prolonged spatial uncertainty.